Influence of orthokeratology lenses on the state of accommodative function in children with myopia - T. E. Tsybulskaya (Zaporožskij Medicinskij Žurnal)
Aim. It was showed that optimal optical correction have positive effect on the accommodative apparatus of the myopic eye. Absolute and relative accommodation reserves, the nearest point of clear vision in 50 patients (100 eyes) with mild myopia was studied in order to assess the state of the accommodative function of the eyes.